WH-fronting in Malay as a non-structure-preserving rule - Kader, Mahudi Bin Haji (1979)
A number of different alternative positions where a fronted 'Wh word' + kah in Malay could be posted has been considered. It is demontrated that , in malay, a fronted 'Wh word + kah does not replace a WH , it dies not fill an empty node dominated by COMP, neither does it occupy a position generable in the phrase structure rules. Instead it is shown that a fronted 'Wh word + kah is simply sister adjoined to thw root S. As such, in Malay simplex 'Wh-questions', WH-Fronting is not a structure-preserving rule.
Includes bibliographical references (page 83)